2023
DOI: 10.3389/fnins.2023.1186751
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrolysin and repetitive transcranial magnetic stimulation (rTMS) in patients with traumatic brain injury: a three-arm randomized trial

Abstract: IntroductionTraumatic brain injury (TBI) is a major public health problem affecting millions worldwide. Despite significant advances in medical care, there are limited effective interventions for improving cognitive and functional outcomes in TBI patients.MethodsThis randomized controlled trial investigated the safety and efficacy of combining repetitive transcranial magnetic stimulation (rTMS) and Cerebrolysin in improving cognitive and functional outcomes in TBI patients. Ninety-three patients with TBI were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
5
1
Order By: Relevance
“…This may suggest that rTMS did not have any influence on the cerebral electrophysiological changes, while the CRB treatment was an important factor. Despite the previously reported correlation between increased DAR/DTABR and poorer functional and cognitive outcomes [ 40 , 41 , 44 , 45 ], our qEEG results correlated with improved, non-significant results at the neurocognitive tests for the CRB + TMS and CRB + sham groups [ 25 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This may suggest that rTMS did not have any influence on the cerebral electrophysiological changes, while the CRB treatment was an important factor. Despite the previously reported correlation between increased DAR/DTABR and poorer functional and cognitive outcomes [ 40 , 41 , 44 , 45 ], our qEEG results correlated with improved, non-significant results at the neurocognitive tests for the CRB + TMS and CRB + sham groups [ 25 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The 180-day study visits and research therapy were conducted on an outpatient basis at the RoNeuro Institute for Neurological Research and Diagnostic in Cluj-Napoca, Romania. Detailed inclusion and exclusion criteria for patients are outlined in the main article [ 25 ]. Each participant's study schedule included three visits: Study Day 30 for screening and baseline, Study Day 101 for Visit 1, and Study Day 180 for Visit 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another opportunity involves researching and optimizing stimulation parameters for those with mood disorders experiencing cognitive deficits due to mTBI and an adjacent study testing patients with moderate/severe TBI, e.g., [241][242][243][244][245]. Although the focus of this review was solely on cognition, hmTBI is highly comorbid with anxiety or depressive disorders, especially within the Veteran community [246].…”
Section: Cautionary Tale: Getting Ahead Of the Datamentioning
confidence: 99%
“…Using innovative neurophysiological tools and neurotrophic agents, the research activity at the RoNeuro Institute aims to improve functional outcomes and quality of life for patients affected by neurological disorders. In the field of TBI, we have investigated biological markers, pharmacological agents like Cerebrolysin, and non-pharmacological rehabilitation strategies such as repetitive transcranial magnetic stimulation (rTMS) [ 5 , 6 ]. Our studies have demonstrated the positive impact of these interventions on patient recovery, opening new avenues for treatment [ 5 , 6 ].…”
mentioning
confidence: 99%